Breast cancer associated CD169+ macrophages possess broad immunosuppressive functions but enhance antibody secretion by activated B cells - Gunnarsdottir, Frida Björk; Briem, Oscar; Lindgren, Aida Yifter; Källberg, Eva; Andersen, Cajsa; Grenthe, Robert; Rosenqvist, Cassandra; Millrud, Camilla Rydberg; Wallgren, Mika; Viklund, Hannah; Bexell, Daniel; Johansson, Martin E.; et al. (Frontiers in Immunology, 2023)
CD169+ resident macrophages in lymph nodes of breast cancer patients are for unknown reasons associated with a beneficial prognosis. This contrasts CD169+ macrophages present in primary breast tumors (CD169+ TAMs), that correlate with a worse prognosis. We recently showed that these CD169+ TAMs were associated with tertiary lymphoid structures (TLSs) and Tregs in breast cancer. Here, we show that CD169+ TAMs can be monocyte-derived and express a unique mediator profile characterized by type I IFNs, CXCL10, PGE2 and inhibitory co-receptor expression pattern. The CD169+ monocyte-derived macrophages (CD169+ Mo-M) possessed an immunosuppressive function in vitro inhibiting NK, T and B cell proliferation, but enhanced antibody and IL6 secretion in activated B cells. Our findings indicate that CD169+ Mo-M in the primary breast tumor microenvironment are linked to both immunosuppression and TLS functions, with implications for future targeted Mo-M therapy.